Tradisi Kirab Pusaka Eyang Djoego Di Desa Jugo Kecamatan Kesamben Kabupaten Blitar - Lita Kusuma Ningtyas; Yohan Susilo (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
The Eyang Djoego Heritage Carnival tradition is a cultural activity that takes the form of tradition and is carried out every year. The heritage carnival activity was carried out by the community in Jugo Village, Kesamben District, Blitar Regency. This tradition is carried out every year on Legi Sunday in the month of Sela, this is the calculation of dates and months in Javanese tradition. The implementation of the Eyang Djoego Heritage Carnival Tradition is a form of respect for the village ancestor named Eyang Djoego and as a form of community gratitude because with his services he was able to make the residents of Jugo Village live prosperously and have enough because the harvest was so abundant. The focus of this research discusses the origins, procedures, what ubarampe is and the meaning of ubarampe, as well as the function of this traditional activity. This research uses the half-lisa folklore theory of James Danandjadja. The research design used is a qualitative descriptive method, the data sources used in the research are primary and secondary as well as oral and non-verbal data. The results of research from the Eyang Djoego Heritage Carnival Tradition produce meanings that are related to culture. This research discusses the origins of the heritage carnival tradition which originated and developed in Jugo Village. These traditional activities are also enlivened and supported by the people in Jugo Village.